Management of the patient with chronic obstructive airway disease (COPD) in a primary health care context - I. Govender; H. I. Okonta; S. Rangiah; D. Nzaumvila (South African Family Practice)
This paper describes the incidence of chronic obstructive airway disease (COPD), the risk factors, staging, investigations and management of COPD. The differential diagnosis for COPD is also presented as COPD can be confused with other clinical conditions. This paper is presented in practical terms for the clinician working in a primary health care context.